Cultural relevance and linguistic flexibility in literature discussions with emergent bilingual children. Issue 1 (2nd January 2020) - Clark, Amy
ABSTRACT: Spanish-English emergent bilingual children's range of sociocultural and linguistic knowledge have typically gone devalued in relation to school literacy curricula. This case study examines how emergent bilingual children in a second grade one-way immersion dual language classroom draw on their prior cultural-experiential knowledge and dynamic linguistic resources to participate meaningfully during discussions of three authentic fiction texts in Spanish, each with a different level of cultural relevance. Data sources include child data and observational field notes from nine literature discussions of the texts, teacher interview data about discussions, and children's ratings of each text on an adaptation of Ebe's Cultural Relevance Rubric (2010). The examination of how children utilized prior knowledge and bilingual practices in relation to texts determined by the children and teacher to have different levels of cultural relevance, and the focus on discussions of texts in Spanish in a Spanish literacy instructional context are unique. Findings suggest that facilitated discussions of a Spanish text with high cultural relevance and within a flexible linguistic space may provide emergent bilingual children with optimal opportunities to employ prior cultural-experiential resources to participate meaningfully in literature discussions.